Exploring community participation in environmental conservation: insights from Addo Elephant National Park in South Africa - Gotyi, Zamikhaya Gladwell; Handi, Nontle (Frontiers in Conservation Science, 2025)
IntroductionProtected areas (PAs) are central to global biodiversity conservation as they preserve nature, ecosystems, and cultural values. In South Africa, PAs were historically governed through top-down, exclusionary models rooted in colonial legacies that prioritized ecological protection over community rights and knowledge. This approach limited local access, fostered resentment, and increased management challenges such as poaching. Subsequently, conservation discourse has shifted toward participatory governance, community-based natural resource management (CBNRM), and co-management to promote more equitable and sustainable outcomes. This study explores the extent and nature of local community participation in environmental conservation at Addo Elephant National Park in South Africa, using the lens of Community-Based Natural Resource Management (CBNRM). MethodThis was a qualitative case study research, which used purposive and convenient sampling techniques to recruit a sample of 34 participants. Interviews, focus groups and field observations were used to collect data from the participants, which was then thematically analysed.ResultsFindings reveal a tripartite model of community engagement: structured involvement through local NGOs, government-led initiatives such as the Extended Public Works Programme, and isolated voluntary actions driven by cultural values. DiscussionWhile formal participation programmes provide economic incentives that mobilize participation, individual efforts, particularly among women, reflect a deep-rooted, intrinsic commitment to environmental stewardship. The study concludes that sustainable conservation requires an integrated approach that combines institutional support with recognition of informal, culturally embedded practices.